PENGARUH SOSIAL MEDIA MARKETING DAN BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN DENGAN LOYALITAS MEREK SEBAGAI VARIABEL MEDIASI - Maharani, Silvia; Prabowo, Heri; Setiawati, Ira (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the influence of social media marketing and brand equity on purchase decisions with brand loyalty as a mediating variable. The method used is quantitative. A sample of 170 respondents was determined through purposive sampling techniques. Data was collected using a questionnaire that was shared with respondents who had purchased Dewkn_Cake product at least once and analyzed with SmartPLS version 3.0 tools. The results of the study show that social media marketing and brand equity have a positive and significant effect on purchase decisions. Additionally, brand loyalty has been shown to significantly mediate the influence between social media marketing, brand equity, and purchasing decisions. These findings underscore the importance of social media marketing strategies and strengthening brand equity to drive consumer loyalty and improve purchasing decisions